Inter‐annual variability of fruit timing and quantity at Nouragues (French Guiana): insights from hierarchical Bayesian analyses. (16th May 2018) - Mendoza, Irene; Condit, Richard S.; Wright, S. Joseph; Caubère, Adeline; Châtelet, Patrick; Hardy, Isabelle; Forget, Pierre‐Michel
Abstract: The timing and quantity of fruit production are major determinants of the functioning of a forest community, but simultaneous analyses of both are rare. We analyzed a ten‐year dataset (2001–2011) of fruit production for 45 tree and liana species from the Nouragues rain forest, French Guiana. We developed a hierarchical Bayesian approach to determine variation in the timing and quantity of fruit production. Our analysis accommodates missing censuses and quantifies variation at seasonal and inter‐annual scales. The fruiting peak of 22 of 45 species occurred during the peak of the rainy season, which is typical for central and eastern Amazon. The timing and quantity of fruit production varied substantially across years in most species, with greater variation in quantity than in timing. The timing of fruit production varied from continuously fruiting species to mast fruiting species that had two or more consecutive years without fruit production. Fully 40% of species were mast fruiting species. The seasonal timing and inter‐annual variation in fruiting were unrelated to seed dispersal mode across species. We saw no evidence for directional change in the level of fruit production, the timing of fruit production, or their variances; however, 10 yr is a short record for such analyses.